THE EFFECTIVENESS OF CLASS PRESERVING NOMINALIZER SUFFIXES IN NOMINALIZATION PROCESS WITH REFERENCE TO ENGLISH AND CENTRAL KURDISH - Omer Hama Salih, Garmian; Aadulla Hasan, Jalal (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The current paper copes with class maintaining nominalizer suffixes in English and central Kurdish languages. The process by which complex nouns can be derived from other nouns. In this study, a comparative morphological approach is adopted. Furthermore, generally it encompasses the background knowledge about nouns, types of nouns and the notion of nominalization as well. This work aims at appraising the importance of nominalizers in noun formation as a derivational Process. Likewise, this research strives to expose the points that both languages share and the points that they are distinct concerning the notion of nominalizer suffixes and stipulates their origins too. Moreover, it intends at determining types of derived nouns that they produce and the meanings that they tolerate. To accomplish the objectives, this probe logically hypothesizes that nominalizer suffixes are dominant, productive and significant phenomenon in extending the vocabulary of both languages. Besides, it also anticipates that, certain range of resemblances and differences might be exhibited regarding this process in both languages. The results announce that Kurdish language nominalizers are more significant and prominent than English nominalizers in regard to number and the notions that they sustain. Furthermore, the study affirms that the uttermost of the denominal nominalizers and nominal bases in English language were borrowed from other languages whereas in Kurdish most of them are native and original.